PERBANDINGAN MODEL ALTMAN, SPRINGATE, ZMIJEWSKI DAN GROVER SEBAGAI PREDIKSI FINANCIAL DISTRESS (Studi Pada Perusahaan Sektor Infrastruktur yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2020-2022) - Erny Amriani Asmin; Ismartaya -; Dwi Gemina; Istiyanah - (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The financial performance of a company is the prospect or future, the potential growth and development for the company. The economic situation can change, this affects the activities and performance of companies, both small and large companies. One of the company's responsibilities is to produce good performance to avoid financial distress. This research aims to find out whether there are differences in predictions between the Altman, Springate, Zmijewski and Grover models as predictions of financial distress and to find out whether the Springate model is the most accurate prediction of financial distress. This research is quantitative research. The data source is secondary data from infrastructure sector companies listed on the IDX in 2020-2022. Sampling used a nonprobability method with purposive sampling technique. The sample consisted of 44 companies. The data analysis technique uses the Kruskal-Wallis H Test with the SPSS 25 program and the Accuracy Level Test. The results of the research reveal that there are significant differences between the Altman, Springate, Zmijewski and Grover calculation models for predicting financial distress and Springate is the most accurate financial distress prediction model in predicting financial distress with an accuracy level of 73%.